2018
DOI: 10.2298/abs170731037s
|View full text |Cite
|
Sign up to set email alerts
|

The effects of β-lactam antibiotics and hygromycin B on de novo shoot organogenesis in apple cv. Golden Delicious

Abstract: Since the genetic transformation of the apple is strongly genotype-dependent and generally inefficient, the evaluation of factors affecting shoot regeneration are crucial for the establishment of a successful transformation process. In this report, we evaluated the effects of the β-lactam antibiotics meropenem and timentin on in vitro regeneration via de novo shoot organogenesis from leaf explants of apple cv. Golden Delicious, as well as on the growth of the Agrobacterium tumefaciens strain EHA 105, and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…The effects of antibiotics on shoot growth and development can be important when the objective is to produce transgenic plants. Stanišić et al (2018), using the protocol of Mitić et al (2012) for 'Golden Delicious', noted that when 300 mg/l cefotaxime was used, shoot growth improved, increasing shoot number per explant from 7.67 to 9.69 in the control, whereas other β-lactam antibiotics (meropenem and timentin) stunted shoot growth, a similar response that chrysanthemum and tobacco had displayed when several aminoglycoside antibiotics were tested (Teixeira da Silva and Fukai 2003). Pathak and Dhawan (2012b) found that the growth of rootstock M7 and MM111 shoots could be supported on medium containing between 1 and 5% fructose, glucose, mannitol, sorbitol and sucrose, with the most effective concentration resulting in longest shoots and greatest productivity arising from 4% sucrose and sorbitol for M7 and MM111, respectively.…”
Section: Plant Growth Regulatorsmentioning
confidence: 98%
See 1 more Smart Citation
“…The effects of antibiotics on shoot growth and development can be important when the objective is to produce transgenic plants. Stanišić et al (2018), using the protocol of Mitić et al (2012) for 'Golden Delicious', noted that when 300 mg/l cefotaxime was used, shoot growth improved, increasing shoot number per explant from 7.67 to 9.69 in the control, whereas other β-lactam antibiotics (meropenem and timentin) stunted shoot growth, a similar response that chrysanthemum and tobacco had displayed when several aminoglycoside antibiotics were tested (Teixeira da Silva and Fukai 2003). Pathak and Dhawan (2012b) found that the growth of rootstock M7 and MM111 shoots could be supported on medium containing between 1 and 5% fructose, glucose, mannitol, sorbitol and sucrose, with the most effective concentration resulting in longest shoots and greatest productivity arising from 4% sucrose and sorbitol for M7 and MM111, respectively.…”
Section: Plant Growth Regulatorsmentioning
confidence: 98%
“…Alayón-Luaces et al 2012Shoot tips from 10 cm scionwood cuttings → RTW time NR → 70% EtOH 1 min → 5% NaOCl + 0.1% Tween-20 + 150 mg/l AA 10 min → SDW + 150 mg/l AA 4× Kereša et al (2012) Bud (0.8-1.5 cm) rinsed in water with detergent 10 min → 4% NaOCl 20 min → SDW 5× Mitić et al (2012); Stanišić et al (2018) Seeds → 70% EtOH 1 min → 0.1% HgCl 2 10 min → SDW 3× Dai et al (2013Dai et al ( , 2014 Shoot tips (5-10 mm) → Tween-80 time NR → DW 3-4 × → meristems excised from shoot tips → 0.01% HgCl 2 1 min → SDW 4-5× Mir et al (2013) Single node cuttings → soapy RTW → fungicides (2 g/l each of Benomile + Ridomile) 20 min → 2014Axillary buds (0.2-0.6 cm) → tap water + 0.05% Tween-20 10 min → Zhang et al (2014) Shoot tips → egg yolks + 20% NaOCl + 2 drops of Tween-20 20 min →…”
Section: Sdw 4×mentioning
confidence: 99%
“…The medium supplemented with antibiotics such as β-lactam antibiotics and tetracycline has been reported to result in higher regeneration capacity as compared with untreated explants [ 189 , 190 ]. Despite the successful application of antibiotics to suppress bacterial growth in vitro, excessive and regular use of them is detrimental to the regeneration process and results in a reduced regeneration ability of tissue cultures [ 191 ].…”
Section: Physiological Responses Of Plant Regenerationmentioning
confidence: 99%
“…Their concentration should be optimized before transformation to determine an effective dose leading to plants regeneration as well as a lethal dose for Agrobacterium . This step is extremely important due to the fact that the prolonged presence of Agrobacterium in plant tissues affects the growth and development of explants and can even cause necrosis and consequently their death (Stanišić et al 2018 ). Furthermore, presence of Agrobacterium in tissue of putative transformants could result in false positive results in the molecular analyses.…”
Section: Genetic Transformation Of Brassica Oleracea Var Cmentioning
confidence: 99%
“…In addition, elimination of Agrobacterium from transformed plants prevents the possibility of accidental release of transgenes to the environment when transformants are transferred to the soil (Tambarussi et al 2015 ). Beta-lactam antibiotics (e.g., carbenicillin, cefotaxime and timentin) are most commonly used for combating Agrobacteria after genetic transformation (Stanišić et al 2018 ). Due to the difficulty in the transformation of cabbage, only few papers related to this subject were published.…”
Section: Genetic Transformation Of Brassica Oleracea Var Cmentioning
confidence: 99%